Legal rulings on medical issues: a comparative study between the Malaysian and Islamic Law - Jahn Kassim, Puteri Nemie (Kulliyyah of Medicine, International Islamic University Malaysia, kuantan, 2018)
The medical profession is amongst the professions that offer tremendous benefit to the entire humanity. Nevertheless, the responsibilities that they have to undertake in their daily practice are constantly increasing as they deal with two most precious commodities of mankind, which is life and health. The demands for accountability when ‘the consequences of an action are considered not to be at par with the expectations’ has become a common trend within the society recently. Law, being an instrument of social regulation, intervenes to establish the rights and responsibilities in medical practice to determine the boundaries of rightful conducts in areas where there exist conflicts of moral, ethical and religious issues. Therefore, it is pertinent for Muslim doctors to keep abreast with the developing law that is governing their practices and at the same time, to ensure that any deliberations flourish within the confines of Islamic law. By employing qualitative research method, namely, doctrinal analysis, this paper seeks to discuss the legal rulings from the Malaysian and Islamic law perspectives relating to significant and current medical issues such as negligence, confidentiality, assisted reproductive technologies, abortion, euthanasia, organ transplantation and sterilisation.